An Impact on the Financial Performance of Employees Cooperative Thrift and Credit Societies - Edwin Gnanadhas, M.; Geetha, P. (Indian Journal of Finance, 2009)
Cooperatives play a vital role in the economic development of the nation. Since independence; the cooperative sector has made remarkable progress which has also resulted in certain weaknesses. If the cooperative sector fails to adopt itself to the new environment it may not survive. Hitherto, a majority of them existed because of government support. The Globalisation of economy, deregulation of interest rates, and rapid development of information technology and introduction of prudential norms has introduced a new element of competition. In the light of this changing scenario, cooperative societies have to prepare themselves to face these challenges.